A New Modular Phosphite‐Pyridine Ligand Library for Asymmetric Pd‐Catalyzed Allylic Substitution Reactions: A Study of the Key Pd‐π‐Allyl Intermediates. Issue 7 (7th January 2013) - Mazuela, Javier; Pàmies, Oscar; Diéguez, Montserrat
Abstract A library of phosphite‐pyridine ligands L1–L12 a–g has been successfully applied for the first time in the Pd‐catalyzed allylic substitution reactions of several di‐ and trisubstituted substrates by using a wide range of C, N and O nucleophiles, among which are the little studied α‐substituted malonates, β‐diketones, and alkyl alcohols. The highly modular nature of this ligand library enables the substituents/configuration at the ligand backbone, and the substituents/configurations at the biaryl phosphite moiety to be easily and systematically varied. We found that the introduction of an enantiopure biaryl phosphite moiety played an essential role in increasing the versatility of the Pd‐catalytic systems. Enantioselectivities were therefore high for several hindered and unhindered di‐ and trisubstituted substrates by using a wide range of C, N and O nucleophiles. Of particular note were the high enantioselectivities (up to>99 % ee) and high activities obtained for the trisubstituted substrates S6 and S7, which compare favorably with the best that have been reported in the literature. We have also extended the use of these new catalytic systems in alternative environmentally friendly solvents such as propylene carbonate and ionic liquids. Studies on the Pd‐π‐allyl intermediates provide a deeper understanding of the effect of ligand parameters on the origin of enantioselectivity.